Hydrothermally carbonized xylem sap for use in chemosensors, on and off switches, and memory devices - Semeniuk, Maria; Tjong, Jimi; Lu, Zheng-Hong; Sain, Mohini (Energy reports, 2022)
Multiple novel chemo sensor devices were created using hydrothermally synthesized fluorescent carbon produced from xylem sap. Most notably, UV light shone on the carbon can be used to selectively detect Fe3＋ ions and pH by the “naked eye” instantly, a first for xylem-syrup-derived hydrocarbons. A large stroke shift is present with outstanding photo-stability, sensitivity. NOT, AND, and NOR logic gates were derived using this novel behaviour, and implemented in proof-of-concept applications including an on–off switch, a chemo sensor, and a memory device based on the fundamentals of transistors and hydrochar’s structural attributes. For the first time, characteristic crystalline sp2 carbon was observed in hydrochar xylem syrup, the results confirm 0.34 nm interlayer spacing and Raman spectroscopy displays an ID/IG ratio of 0.22 similar to graphitic structures. This material designed chemo sensor devices based on logic gates which have a significant broad potential to act as smart nano devices and displace traditional metal–oxide–semiconductor field-effect transistor (MOSFET) based circuits. The field of renewable hydrocarbon is the subject of a considerable, widening range of interest for a diverse field of applications that can be applied in innovative batteries, sensors, smart materials, healthcare and environmental monitoring. [Display omitted] •Multiple chemo sensor devices from hydrothermally carbonized xylem sap.•Crystalline sp2 carbon with 0.34 nm interlayer spacing and an ID/IG ratio of 0.22.•Selectively detect with high sensitivity Fe3＋ ions and pH by the “naked eye”.•Fluorescence proof-of-concept of on–off switch, a chemo sensor and a memory device.•Logic gates displace traditional metal–oxide–semiconductor field-effect transistors.